De constructione – de consecratione ecclesiae Hoyensis (1066) - George, Philippe (Hortus Artium Medievalium, 2014)
Abstract All the history books on the Middle Ages mention the famous « Charter of Huy from 1066 », the oldest surviving example of a freedoms charter north of the Alps. In granting this freedoms charter to the citizens of Huy, Théoduin, the Bishop of Liège, (1048- 1075) obtained in exchange the financial resources to achieve his objectives: the rebuilding of Huy-sur-Meuse and its collegiate church, which had been destroyed and ruined in 1053 by the count of Flanders. At the same time, the prelate was readying his own tomb. On August 1066, the grandiose inauguration ceremonies were held in the new church. The eulogy of this monument of Huy De constructione - de consecratione ecclesiae Hoyensis is perhaps missing, but the interdisciplinary approach makes it possible today to reconsider the matter: history, hagiography, architecture, art, liturgy and the sacred spatialization.